PENGARUH SENAM POCO-POCO TERHADAP KADAR KOLESTEROL HIGH DENSITY LIPOPROTEIN DARAH - Arif, Ade W.; Wongkar, Djon; Ticoalu, Shane H. R. (e-Biomedik, 2015)
Abstract: High Density Lipoprotein (HDL) is denser than other types of cholesterol. Blood HDL cholesterol protects the inner wall (endothelium) of blood vessels. Exercise such as Poco-poco dance can increase the HDL cholesterol level. This study aimed to obtainthe the effect of Poco-poco dance on blood HDL cholesterol level. This was an experimental study with one group pre and post test design. Subjects were 25 Pharmacy female students, Faculty of Mathematics and Sciences, Sam Ratulangi University. Subjects were selected by purposive sampling method. Data were analyzed by using paired T test. The results showed that the average of blood HDL cholesterol level of subjects before training was 57,76 mg/dL and increased to 58,44 mg/dL after 4 weeks of training. The statistical analysis showed a p value >0.05. Conclusion: There was no statistically significant increase in HDL cholesterol level after 4 weeks of Poco-poco dance.Keywords: Poco-poco dance, high density lipoproteinAbstrak: High Density Lipoprotein (HDL) merupakan kolesterol dengan partikel yang lebih padat dibandingkan kolesterol jenis lain. Kolesterol HDL darah berperan sebagai pemelihara dinding bagian dalam (lapisan endotel) pembuluh darah. Salah satu cara untuk meningkatkan kadar kolesterol HDL darah ialah dengan melakukan aktivitas fisik, antara lain senam poco-poco. Penelitian ini bertujuan untuk mengetahui pengaruh senam poco-poco terhadap kadar kolesterol HDL darah. Penelitian ini bersifat eksperimental dengan rancangan one group pre and post test. Sampel penelitian ialah mahasiswa Program Studi Farmasi Fakultas MIPA Universitas Sam Ratulangi Manado sebanyak 25 orang yang ditentukan dengan cara purposive sampling. Data dianalisis dengan uji T berpasangan. Setelah dilakukan latihan selama 4 minggu diperoleh hasil rerata kolesterol HDL sebelum latihan 57,76 mg/dL dan sesudah latihan 58,44 mg/dL. Analisis statistik menunjukkan nilai p >0,05. Simpulan: Terjadi peningkatan kadar kolesterol HDL darah setelah empat minggu senam poco-poco namun secara statistik tidak bermakna.Kata kunci: senam poco-poco, high density lipoprotein